Consistency of recommendations from clinical practice guidelines for the management of critically ill COVID-19 patients. Issue 1 (31st July 2020) - Kow, Chia Siang; Capstick, Toby; Zaidi, Syed Tabish Razi; Hasan, Syed Shahzad
Abstract : Background: A significant knowledge gap exists for the management of critically ill patients with coronavirus disease 2019 (COVID-19). This study aimed to systematically investigate the consistency of recommendations from the available clinical practice guidelines (CPGs) to those of the WHO on the management of critically ill COVID-19 patients. Methods: We examined CPGs and UpToDate point-of-care resources on the management of critically ill COVID-19 patients that had been published as of 30 April 2020 and compared them against the CPG by the WHO. The main outcome was the rate of consistency among CPGs for the management of critically ill COVID-19 patients. Sensitivity analyses were conducted by excluding recommendation statements that were described as insufficient evidence and by excluding single CPGs one at a time. Results: Thirteen reference recommendations derived from the CPG of the WHO were generated using discrete and unambiguous specifications of the population, intervention, and comparison states. Across CPGs, the rate of consistency in direction with the WHO is 7.7%. When insufficient evidence codings were excluded, the rate of consistency increased substantially to 61.5%. The results of a leave-one-out sensitivity analysis suggested that the UpToDate recommendation source could explain the inconsistency. Consistency in direction rates changed by an absolute 23.1% (from 1/13 (7.7%) to 4/13 (30.8%)) if UpToDate was removed. Conclusions: We observed inconsistencies between some recommendations of the CPGs and those of the WHO. These inconsistencies should best be addressed by consensus among the relevant bodies to avoid confusion in clinical practice while awaiting clinical trials to inform us of the best practice.